2023
DOI: 10.1038/s41467-023-36383-6
|View full text |Cite
|
Sign up to set email alerts
|

Cartography of Genomic Interactions Enables Deep Analysis of Single-Cell Expression Data

Abstract: Remarkable advances in single cell genomics have presented unique challenges and opportunities for interrogating a wealth of biomedical inquiries. High dimensional genomic data are inherently complex because of intertwined relationships among the genes. Existing methods, including emerging deep learning-based approaches, do not consider the underlying biological characteristics during data processing, which greatly compromises the performance of data analysis and hinders the maximal utilization of state-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Most of the traditional and state-of-the-art techniques 7 , 8 , 50 , 51 , 52 , 53 , 54 , 55 , 56 perform the analysis of developmental and differentiation trajectories by first finding the data clusters. In these analyses, the idea is to first find the clusters, and then a minimum spanning tree is constructed on the clusters to determine the number and rough shape of lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the traditional and state-of-the-art techniques 7 , 8 , 50 , 51 , 52 , 53 , 54 , 55 , 56 perform the analysis of developmental and differentiation trajectories by first finding the data clusters. In these analyses, the idea is to first find the clusters, and then a minimum spanning tree is constructed on the clusters to determine the number and rough shape of lineages.…”
Section: Discussionmentioning
confidence: 99%
“…8). It is noteworthy that like many other data analysis techniques such as PCA, FEM, GSE 50 , CCSF 39 , t-SNE, and UMAP, interactive relationships of the components inside an HD feature point are not considered explicitly during the MDA embedding process 51 . For some special applications such as the assessment of image similarity in a low dimensional embedding, DNN-based manifold learning techniques like Deep Manifold Embedding Method (DMEM) 52 and Deep Local-flatness Manifold Embedding (DLME) 53 could be used.…”
Section: Discussionmentioning
confidence: 99%
“…In Liu et al [23], low accuracy is obtained to more number of redundant features. Islam et al [24] and Xiao et al [25] reported high accuracies due to the applied deep learning methods. Abdulla et al [30] has proposed a cost sensitive feature selection method with accuracy in the range of 95%.…”
Section: Review Of Previous Workmentioning
confidence: 99%